ANALISIS FRAMING PEMBERITAAN ISU DINASTI POLITIK JOKOWI PADA PEMILIHAN PRESIDEN 2024 DI KOMPAS. COM PERIODE OKTOBER - Pinkki Dwi Oetami; Fikriana Mahar Rizqi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The news about Jokowi's political dynasty became one of the most widely reported topics by Kompas.com in October 2023. This study aims to analyze the framing of the news about President Joko Widodo's (Jokowi) political dynasty in the 2024 Presidential Election in the online media Kompas.com for the October 2023 period. The phenomenon of political dynasty was highlighted due to the involvement of Jokowi's family in the national political sphere, especially the nomination of Gibran Rakabuming Raka as a vice presidential candidate accompanying Prabowo Subianto. The research method used was qualitative with a descriptive approach, using the framing analysis model of Zhongdang Pan and Gerald M. Kosicki which includes four structures: syntax, script, thematic, and rhetorical. The research objects were five main articles on Kompas.com that discussed the issue of Jokowi's political dynasty during that period. The results showed that Kompas.com presented relatively neutral and balanced news by presenting pro and con viewpoints, using polite language and paying attention to journalistic values. Kompas.com's news framing plays a role in shaping public perception regarding Jokowi's political dynasty, particularly regarding the nomination of Gibran Rakabuming Raka as a vice presidential candidate. These reports emphasize the controversial Constitutional Court ruling, Jokowi's changing stance, the public response, and his defense against accusations of political dynasty. This research emphasizes the media's role as a crucial actor in constructing political reality and the influence of framing on the dynamics of national political news coverage.